Shared CaM‐ and S100A1‐binding epitopes in the distal TRPM4 N terminus. (29th December 2017) - Bousova, Kristyna; Herman, Petr; Vecer, Jaroslav; Bednarova, Lucie; Monincova, Lenka; Majer, Pavel; Vyklicky, Ladislav; Vondrasek, Jiri; Teisinger, Jan
Abstract : The transient receptor potential channel of melastatin 4 (TRPM4) belongs to a group of large ion receptors that are involved in countless cell signalling cascades. This unique member is ubiquitously expressed in many human tissues, especially in cardiomyocytes, where it plays an important role in cardiovascular processes. Transient receptor potential channels (TRPs) are usually constituted by intracellular N‐ and C‐ termini, which serve as mediators affecting allosteric modulation of channels, resulting in the regulation of the channel function. The TRPs tails contain a number of conserved epitopes that specifically bind the intracellular modulators. Here, we identify new binding sites for the calmodulin (CaM) and S100 calcium‐binding protein A1 (S100A1), located in the very distal part of the TRPM4 N terminus. We have used chemically synthesized peptides of the TRPM4, mimicking the binding epitopes, along with fluorescence methods to determine and specify CaM‐ and S100A1‐binding sites. We have found that the ligands binding epitopes at the TRPM4 N terminus overlap, but the interacting mechanism of both complexes is probably different. The molecular models supported by data from the fluorescence method confirmed that the complexes formations are mediated by the positively charged (R139, R140, R144) and hydrophobic (L134, L138, V143) residues present at the TRPM4 N terminus‐binding epitopes. The data suggest that the molecular complexes of TRPM4/CaM and TRPM4/S100A1 would lead to the modulation of the channel functions. Abstract : Distal intracellular N termini of TRPM4 ion channel contain CaM and S100A1 overlapping binding epitopes. The interacting mechanism of both complexes is apparently different.